Condições de oferta e qualidade do ensino do município de Ananindeua-PA no contexto do FUNDEB (2007- 2015) - NASCIMENTO, Yasmim Edith Carvalho do (2019)
This study exploratory aims to analyze the condition of teaching efectiveness in terms of investiment in basic education of the municipality network of Ananindeua district and its conditions of quality and offer during the validity period of FUNDEB (2007 to 2015). The inquiry process that guided the research paradigm was the qualitative one, being organized to articulate the quantitative informations of the social indicators, of financing, educational offer and the quality in municipality. The reserch results revelal that, in the analyzed period: 1 – there was an improvement in the social indicators of the municipality expressed by the total population data (1.6%), IDHM (0.718 – high), PIB (12.2%) and PIB per capta (12.1%); 2 – growth of liquid expenses in the education function (13.9%) and elementary school expediture committed (9.6%) and pre-school education (151.8%), as well as FUNDEB revenue (14,6%); 3 – in terms of enrollment, there was a greater growth in the private school system (23.6% in pre-school, 17% in elementary education) comparing the municipal network (18.8%, 4.8% in pre-school) and state (did not abstain an average growth); In relation to the number of schools, there was great growth in the private network (30.1% in pre-school, 33.2% in the elementary school than in the state network (did not obtain a mean of growth) and municipality (6.5% in pre-school, 19.1% in elementary school), and in relation to the number of teachers, in pre-school education, the municipality network present highest growth (101) compared to the state network (0) and private network (92), however in the elementary school the private network (687) present the greatest increase, compared to the municipal network (88) and the state network (520); 4- in relation to the school performance, the private school system has the best rates (0.5% of approval, 14.5% of disapproval and 22.5% of school dropout), compared to the municipal network (3,4 % of approval, 11.5% of disapproval and 7.4% of school truancy), and state (2.9% of approval, 11.9% of disapproval and 6.3% of school truancy). About the IDEB data, it was verified that municipality achived most of the estabilished goals. Considering the progress of municipality – with resource growth and its redistribution process from FUNDEB – in condition of quality and offer, none of them were fullfill by the municipality of Ananindeua. Given the importance of the policy in the field of municipality education network, it is necessary to fight for its restructuring and extention, increasing the Union’s contribution and ensuring the effectiveness of the righ to puplic education and quality.